Analysis of Deflector Variations to Improve Performance and Determine the Force of the Darrieus Turbine Using CFD Software - Susanto, Edy; Arie Hadiansyah, Muhammad; Sinambela, Hotdian; Erwin, Erwin (DINAMIS, 2025)
This research focuses on developing deflectors to improve the performance of Darrieus turbines, a type of vertical wind turbine known for its efficiency in the conversion of wind energy into mechanical energy. The main objective of this research is to test different deflector shapes to optimize the airflow entering the turbine blades and improve the efficiency and power output of the turbine. In this study, various deflector designs including semicircular, triangular, rectangular, hexagonal, and pentagonal shapes were examined to determine their effectiveness in directing and accelerating airflow to the turbine blades. The research method involved aerodynamic simulations using CFD software. The results showed that the semicircular-shaped deflector provided significant performance improvement compared to the other shapes. These deflectors successfully reduced turbulence and drag, and accelerated the airflow entering the turbine blades, thereby increasing the overall power output of the Darrieus turbine. In addition, the analysis shows that at 17.5, 10.5, and 8.5 m/s calculations, at 8.5 m/s wind speed calculation, the air speed can reach 30.1% with a force of 7.30344 N, and 10.5 m/s speed can reach 24.33% with a force of 11.361 N, and 17.8 m/s wind speed can reach 20.67% with 25.638 N force.